Critical Role of c-IAP-2 in Mediating Mechanisms of Resistance to HIV-Vpr-induced Apoptosis in Human Monocytic Cells - Saxena, Mansi (Université d'Ottawa / University of Ottawa, 2013)
Monocytic cells survive HIV replication and consequent cytopathic effects because of their decreased sensitivity to HIV-induced apoptosis. However, the mechanism underlying this resistance to apoptosis remains poorly understood. I hypothesized that exposure to microbial products, translocated from the gut, may confer anti-apoptotic properties in human monocytic cells through interaction with their corresponding Toll-like receptors (TLRs). Using HIV-Vpr(52-96) peptide as a model apoptosis-inducing agent, I demonstrated that unlike monocyte-derived macrophages, undifferentiated primary human monocytes and pro-monocytic THP-1 cells are highly susceptible to Vpr(52-96)-induced apoptosis. Interestingly, monocytes and THP-1 cells stimulated with TLR-9 agonists, CpG and E.coli DNA, induced almost complete resistance to Vpr(52-96)-induced apoptosis albiet via a TLR-9 independent signaling pathway. Moreover, CpG and E.coli DNA selectively induced the anti- apoptotic Inhibitor of Apoptosis Protein-2 (c-IAP-2) and inhibition of the c-IAP-2 gene by either specific siRNAs or synthetic second mitochondrial activator of caspases (Smac) mimetic reversed CpG-induced resistance against Vpr(52-96)-mediated apoptosis. I demonstrated that c-IAP-2 was regulated by the c-Jun N terminal kinase (JNK) and the calcium signaling pathway in particular the calmodulin-dependent protein kinase-II (CaMK-II). Furthermore, inhibition of JNK and the calcium signaling including CaMK-II by either pharmacological inhibitors or their specific siRNAs reversed CpG-induced protection against Vpr(52-96)-mediated apoptosis. I also showed that CpG-induced JNK phosphorylation through activation of calcium signaling pathway.
Keywords: HIV-Vpr; monocytes; c-IAP-2; bacterial DNA